2021
DOI: 10.1038/s41467-021-26466-7
|View full text |Cite
|
Sign up to set email alerts
|

Precise measurements of chromatin diffusion dynamics by modeling using Gaussian processes

Abstract: The spatiotemporal organization of chromatin influences many nuclear processes: from chromosome segregation to transcriptional regulation. To get a deeper understanding of these processes, it is essential to go beyond static viewpoints of chromosome structures, to accurately characterize chromatin’s diffusion properties. We present GP-FBM: a computational framework based on Gaussian processes and fractional Brownian motion to extract diffusion properties from stochastic trajectories of labeled chromatin loci. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 66 publications
2
42
0
Order By: Relevance
“…It is clear that more DNA-protein interactions are possible during longer time windows, since proteins have more time to travel longer distances to reach their target. The distance is denoted by the random variable R which has the expected squared displacement with diffusion constant [ 14 , 16 , 17 , 19 , 35 ]. Consequently, the searched volume is , where k ′ is a scaling constant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that more DNA-protein interactions are possible during longer time windows, since proteins have more time to travel longer distances to reach their target. The distance is denoted by the random variable R which has the expected squared displacement with diffusion constant [ 14 , 16 , 17 , 19 , 35 ]. Consequently, the searched volume is , where k ′ is a scaling constant.…”
Section: Discussionmentioning
confidence: 99%
“…Repair happens through the collective working of several proteins, which need to move through the environment and find their target. Nuclear diffusion has been studied and modelled in detail in different contexts such as chromatin [15][16][17] and protein movements [13,35], including the repair protein Rad4 [19]. It is clear that more DNA-protein interactions are possible during longer time windows, since proteins have more time to travel longer distances to reach their target.…”
Section: Applying the Cpd Repair Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For these two ESC lines, we imaged the labeled loci at high temporal resolution (500 ms per frame) in 2D with spinning disk confocal microscopy, using a set of optimized affine transformations to correct for chromatic aberrations and control for camera misalignment. Further enhancement of spot centroid localization was performed by fitting a 2D Gaussian shape to a precision of ~30 nm 25 . In line with previous high-throughput DNA FISH studies 52,53 , median inter-probe distances demonstrated a large cell-to-cell heterogeneity, varying from 69-286 nm (n = 72) for Sox2-SCR distances and from 71-426 nm (n = 49) for the control regions (Fig 1e; Table S1).…”
Section: Enhancer-promoter Proximity Is Frequently Maintained At the ...mentioning
confidence: 99%
“…This is often characterized as subdiffusive movement, whereby the mean squared displacement (MSD) of the genomic element follows the relationship with time, t: MSD ∝ Dt α where D is the diffusion coefficient (a proxy for diffusive speed) and α, the anomalous exponent, is smaller than the value of 1 found in classical Brownian diffusion. Initial studies of randomly inserted tags suggested that heterochromatin was inherently less mobile than euchromatin in yeast 24 , but we recently reported significant locus-specific differences in chromatin diffusive properties at euchromatic regions in mouse embryonic stem cells (ESCs), suggesting finer-scale modulation of chromatin dynamics, potentially linked to underlying function 25 . As methods for tracking specific genomic regions in vivo has recently become available, researchers have asked whether the transcriptional activity of genes affects their mobility.…”
Section: Introductionmentioning
confidence: 99%